Hubungan masa dan kos projek : algoritma dan kategori kos - Mat Yatim, Safie (Penerbit UTM Press, 1990)
This paper discusses network analysis approach in analysing activities and projects costs. The relationship between activities time and cost, and the algorithm which determine scheduling times for each activity with the least project cost. Furthermore, the relationship between costs, resources and time of the project will also be discussed.